Application of the Fuzzy Model Theory for Modeling QA-Systems - Yakhyaeva, Gulnara; Karmanova, Anastosia; Ershov, Aleksei (Computing and Informatics, 2022)
The work is devoted to the description of the question-answer system QA-RiskPanel, which provides means of determining and forecasting the risks related to computer attacks. The QA-RiskPanel system uses a constantly updated database of previous computer attacks as a source of knowledge. We thus guarantee the most up-to-date risk prediction. The ontological approach to the formalization of the object domain allows the analysis of risks at various levels of specification/generalization. In this paper we provide a model-theoretic formalization of the Knowledge Base of the described object domain. Then we describe the classification of question types, which are probabilistic in this system. Finally we present algorithms for finding the answers to all question types of our classification.